Total Syntheses of Kealiinines A-C - Das, Jayanta (2012)
[Image: see text] Short total syntheses of the Leucetta-derived alkaloids, kealiinines A-C, have been accomplished using an intramolecular Friedel-Crafts-dehydration sequence of a bis benzylic diol. The precursor diol was obtained through a series of position specific Grignard reactions from 1-methyl-4,5-diiodoimidazole. C2-Azidation and hydrogenation of the azide then provided the reported structures of kealiinines A-C. While the (1)H NMR data did not completely match for these materials, the HPLC data were consistent with the assigned structure of these materials.